Proud Kentuckian : John C. Breckinridge, 1821-1875 - Heck, Frank Hopkins (Book collections on Project MUSE., 2009)
In his brief life John C. Breckinridge embraced the roles of lawyer, politician, statesman, soldier, exile, and businessman. An imposing and tactful man, he was exceptional for evoking both loyal devotion from his followers and generous respect from his opponents during a strife-torn era. Breckinridge's meteoric rise to national prominence began with election to the Kentucky legislature in 1849 and to the United States Congress in 1851. His eloquence earned him the Democratic Party's nomination for the vice presidency in 1856, and he became the youngest man ever to hold that office. Nearing the.